POLA ASUH ORANG TUA DALAM PERKEMBANGAN SIKAP TANGGUNG JAWAB ANAK DI DESA PAREN JEPARA - Hanim Aulia Maghfiroti; Mohammad Kanzunnudin; Sekar Dwi Ardianti (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The goal of this study was to describe the form of children's responsible attitude in Desa Paren, Jepara. This study utilized a descriptive qualitative approach with a case study method. Parental patterns are the ways in which parents fulfill their roles as caretakers, educators, and companions to their children, and can be categorized into three types: democratic, authoritarian, and permissive. A child's responsibility refers to an individual’s attitude toward fulfilling duties and being prepared to bear the consequences of their words and actions. The subjects of this study were four children aged 8–10 years. Data were collected through observations, interviews, and documentation and analyzed qualitatively using the concept references from Miles and Huberman. The results indicated that the type of parenting applied influenced the development of responsibility in children. One child who received an authoritarian upbringing exhibited a low sense of responsibility. One child with a democratic upbringing showed a responsible attitude and the ability to solve problems independently. Two children who experienced permissive parenting demonstrated a reasonably good sense of responsibility.